Increasing the accuracy of absolute measurements at the Argentine Islands geomagnetic observatory of the Ukrainian Antarctic Akademik Vernadsky station - Yu. Sumaruk; A. Marusenkov; A. Neska; V. Korepanov; M. Leonov (Український антарктичний журнал, 2023)
In recent years, the INTERMAGNET geomagnetic observatory Argentine Islands of Ukrainian Antarctic Akademik Vernadsky station, located at Galindez Island, has been modernized. New devices were installed at the observatory: reference three-component fluxgate magnetometer LEMI-025, one-component Mag-01H Fluxgate Declinometer/Inclinometer with non-magnetic Wild T1 Theodolite (DI-magnetometer), and scalar Overhauser magnetometers GSM-19 and GSM-90. These devices have a high resolution and can carry out measurements with greater accuracy. Also, new methods of absolute observations and variation processing were introduced. In 2022, a new DI-magnetometer was installed; it practically did not change the baseline values of the variometer LEMI-025 compared to previous years, which indicates the reliability of the results, but made observations much more convenient. We present the results of processing absolute observations, carried out by different methods. Different techniques of calculating these observations are described, and certain shortcomings or inaccuracies in their application are noted. Recommendations to eliminate the identified shortcomings are proposed. The results of processing of absolute observations by different techniques are compared and the reason for the inconsistency of certain values is found. A new method of calculation of absolute observations is proposed, which was used at the observatory, which showed quite good results. In the new methodology, the calculation of errors of the DI-magnetometer, namely: the zero offset of the magnetic sensor, the azimuth collimation error δ and the elevation collimation error ε of its sensitivity axis relative to the axes of theodolite, is initiated. Analysis of these errors allows identifying and sometimes correcting the errors in absolute measurements. The installation of new devices and the application of new calculation methods made it possible to ensure better data quality and convenience of measurements at the station, to automate the data processing, preparation, and minimizing the influence of the human factor.